Pengaruh Safety Assurance Terhadap Keselamatan Kerja Teknisi di PT. XYZ - Bhima Shakti Arrafat; Gilang Kurnia Chandra; Mursyidin (Langit Biru: Jurnal Ilmiah Aviasi, 2022)
The Safety Management System has 4 pillars, one of the pillars of the safety management system is Safety Assurance. The implementation of a good Safety Management System can affect the level of technician's workplace safety, it is necessary to measure each pillar of the Safety Management System. The pillar of Safety Assurance is something that needs to be measured at PT.XYZ. This study aims to assess safety assurance and improve work safety. The method used in this research is quantitative with descriptive and verification techniques. The data obtained came from questionnaires, observations, documentation, and interviews. The population used as research samples taken are all technicians who work with as many as 36 people in Hangar Hall E PT.XYZ. This study's results indicate a positive effect of 30% between safety assurance and work safety.